Peeping into genomic architecture by re-sequencing of Ochrobactrum intermedium M86 strain during laboratory adapted conditions - Gohil, K. N.; Neurgaonkar, P. S.; Paranjpe, A.; Dastager, S. G.; Dharne, M. S. (Genomics Data, 2016)
Advances in de novo sequencing technologies allow us to track deeper insights into microbial genomes for restructuring events during the course of their evolution inside and outside the host. Bacterial species belonging to Ochrobactrum genus are being reported as emerging, and opportunistic pathogens in this technology driven era probably due to insertion and deletion of genes. The Ochrobactrum intermedium M86 was isolated in 2005 from a case of non-ulcer dyspeptic human stomach followed by its first draft genome sequence in 2009. Here we report re-sequencing of O. intermedium M86 laboratory adapted strain in terms of gain and loss of genes. We also attempted for finer scale genome sequence with 10 times more genome coverage than earlier one followed by comparative evaluation on Ion PGM and Illumina MiSeq. Despite their similarities at genomic level, lab-adapted strain mainly lacked genes encoding for transposase protein, insertion elements family, phage tail-proteins that were not detected in original strain on both chromosomes. Interestingly, a 5 kb indel was detected in chromosome 2 that was absent in original strain mapped with phage integrase gene of Rhizobium spp. and may be acquired and integrated through horizontal gene transfer indicating the gene loss and gene gain phenomenon in this genus. Majority of indel fragments did not match with known genes indicating more bioinformatic dissection of this fragment. Additionally we report genes related to antibiotic resistance, heavy metal tolerance in earlier and re-sequenced strain. Though SNPs detected, there did not span urease and flagellar genes. We also conclude that third generation sequencing technologies might be useful for understanding genomic architecture and re-arrangement of genes in the genome due to their ability of larger coverage that can be used to trace evolutionary aspects in microbial system.